CLINICAL DATA ANALYSIS ON THE ASSOCIATION BETWEEN PERIODONTAL DISEASE, THE DEVELOPMENT OF ORAL SQUAMOUS CELL CARCINOMA AND ORAL POTENTIALLY MALIGNANT DISORDERS - Teodora Bolyarova-Konova; Zornitsa Mihailova; Angel Adamov; Pavel Stanimirov; Samuil Dzhenkov; Konstantin Stamatov; Evgeniy Aleksiev (Journal of IMAB)
Oral cancer is an aggressive disease characterized by low average survival rates. Purpose: To examine the periodontal status in cases of primary oral squamous cell carcinoma (OSCC), oral potentially malignant disorders (OPMD), periodontitis, and healthy individuals in relation to its impact on the development of OSCC and OPMD. Materials/Methods: The study involved 107 individuals with an average age of 54.22±14.38 years (58.9% male, 41.1% female), divided into four groups: Group I – patients with OSCC (n=43); Group II – patients with OPMD (n=21); Group III – patients with periodontitis (n=21); Group IV – healthy individuals (n=22). Results: In the OSCC, OPMD, and periodontitis groups, a significantly lower mean number of existing teeth was observed (16.97, 18, and 22.8, respectively) compared to the healthy group (28.77), along with a tendency for a higher number of missing teeth in OSCC patients compared to those with periodontitis. We found significantly higher values of BOP (Bleeding on Probing) in OSCC patients (67%) compared to those with periodontitis (48.57%) and healthy individuals (9.65%). We consider BOP a potential risk indicator for oral cancer. Conclusions: The trend toward a higher frequency of missing teeth in OSCC patients compared to those with periodontitis is associated with prior infection and inflammation in the oral cavity, which is suspected to play a role in oncogenesis. The significantly higher BOP values in OSCC patients compared to those with periodontitis indicate the influence of inflammation on the development of malignant processes. Periodontal treatment may be an effective approach to reducing the risk of carcinogenesis.